Changing scenario of superficial fungal infection: Emerging resistance, recurrence and remedy in Bangladesh (Bangladesh Critical Care Journal, 2020)
Superficial fungal infections (dermatophytes) affecting skin, nail and hair are the most common infective dermatosis seen in dermatology outpatient clinics. There is a rising prevalence of dermatophytosis, especially in tropical countries like Bangladesh, with a concomitant increase in the number of difficult to treat cases. The reason for this phenomenon is not yet clear, but may be related to inadequate treatment regimen or discontinuation of medication, difficulties in eliminating predisposing factors and sources of re-infection. The pathogenesis and severity of fungal infection depend on various immunological and nonimmunological factors. The rampant use of antifungal therapy in immunocompromised individuals marked the onset of antifungal drug resistance. Fungal resistance can be microbiological or clinical. Genetic alterations in the fungi cause microbiological resistance. Clinical resistance is due to host or drug related factors. All these factors may cause fungal resistance individually or in tandem. Appropriate drug dosing along with antifungal drug susceptibility testing, especially for the dermatophytes isolated from chronic, recurrent cases or those with atypical presentation should be encouraged. Other ways to avoid resistance is the use of combination antifungal therapy. Combination therapy offers advantages in increased synergistic action with enhanced spectrum activity. Finally, newer insights into molecular mechanisms of drug resistance will help in the development of appropriate antifungal therapy. Till then experience based treatment of dermatophytosis is more effective than the standard guideline.Bangladesh Crit Care J September 2020; 8(2): 108-111